Measure for measure - Shakespeare, William, 1564-1616 (Mumbai : Wilco International, 2023)
Measure for Measure is among the most passionately discussed of Shakespeare$1 (Bs plays. In it, a duke temporarily removes himself from governing his city-state, deputizing a member of his administration, Angelo, to enforce the laws more rigorously. Angelo chooses as his first victim Claudio, condemning him to death because he impregnated Juliet before their marriage. Claudio$1 (Bs sister Isabella, who is entering a convent, pleads for her brother$1 (Bs life. Angelo attempts to extort sex from her, but Isabella preserves her chastity. The duke, in disguise, eavesdrops as she tells her brother about Angelo$1 (Bs behavior, then offers to ally himself with her against Angelo.s
Keywords: Chastity -- Drama; Siblings -- Drama